Book Review: Exploration of the Book of Leviticus; God’s Holy-Love Overcome the Problems of Sin’s - Hasahatan Hutahaean (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Paul Hidajat focused on extracting the Book of Leviticus in simple and concise language. The preparation of this book began from a discussion on the social media group (WA) of God's servants from various types of ministries. The discussion was also about the Book of Leviticus and how the application of God's people today should be done. How to understand the Book of Leviticus with provisions that seem difficult to find material and source in the present day? What to do to find replacement material that can't be found? Including how to formulate various worship and practices of burnt offerings, forgiveness of sins or the purification of priests who are indeed in a different context to the present? Using the method of extracting words with the support of cultural context, and the times of writing. Hidajat carefully provides answers to various initial questions in discussions on social media groups through this book. The holiness of the priest today deserves to be maintained so that the continuation of the faith of God's chosen church in the present is maintained. God gives various rules and regulations to guide His people to live holy life and honor God's grace while in it God's love is manifest in the redemption of man. These rules and regulations are given to show God's concern and love for His chosen people.